2008
DOI: 10.1074/jbc.m805114200
|View full text |Cite
|
Sign up to set email alerts
|

Watching the Native Supramolecular Architecture of Photosynthetic Membrane in Red Algae

Abstract: The architecture of the entire photosynthetic membrane network determines, at the supramolecular level, the physiological roles of the photosynthetic protein complexes involved. So far, a precise picture of the native configuration of red algal thylakoids is still lacking. In this work, we investigated the supramolecular architectures of phycobilisomes (PBsomes) and native thylakoid membranes from the unicellular red alga Porphyridium cruentum using atomic force microscopy (AFM) and transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…However, recent investigations have shown that the thylakoid membrane in the unicellular red alga P. cruentum exhibits dense crowding of PBsome complexes [27], [28]. In addition to determining the arrangements of PBsomes on the thylakoid membrane, the supramolecular crowding has also profound implications for the dynamic behavior of PBsomes in P. cruentum : the rapid and long-range movement of PBsomes may be inhibited by the dense packing of membrane surface, and the limited free vertical spacing between opposite thylakoid layers, as well as remarkable steric hindrance, taking into account the large size of individual PBsomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigations have shown that the thylakoid membrane in the unicellular red alga P. cruentum exhibits dense crowding of PBsome complexes [27], [28]. In addition to determining the arrangements of PBsomes on the thylakoid membrane, the supramolecular crowding has also profound implications for the dynamic behavior of PBsomes in P. cruentum : the rapid and long-range movement of PBsomes may be inhibited by the dense packing of membrane surface, and the limited free vertical spacing between opposite thylakoid layers, as well as remarkable steric hindrance, taking into account the large size of individual PBsomes.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of isolated β-carboxysomes were characterized using negative staining TEM as described previously. 65 , 66 Samples were stained with 3% uranyl acetate. Images were recorded using a FEI Tecnai G2 Spirit BioTWIN FEI transmission electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting photosynthetic membranes were then immobilized on freshly cleaved mica substrate for AFM imaging. AFM has demonstrated its extraordinary power in high-resolution imaging of native photosynthetic membranes [ 17 , [22] , [23] , [24] , [25] ] and force measurements to delineate the mechanical unfolding of photosynthetic antenna membrane complexes [ 26 ]. AFM screening showed that the isolated photosynthetic membranes appear as two-dimensional patches with the sizes larger than 150 nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%